2020
DOI: 10.1007/s40858-020-00369-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of natamycin against carrot white mold caused by Sclerotinia sclerotiorum

Abstract: This study was conducted to evaluate inhibitory effect of natamycin against three isolates of Sclerotinia sclerotiorum, the causal agent of carrot white mold in postharvest phase. The results showed that natamycin was able to markedly decrease radial growth and sclerogenesis of three isolates of the pathogen. In addition, natamycin significantly reduced myceliogenic and carpogenic germinations of sclerotia in three isolates. There was a clear positive correlation between natamycin concentration and efficacy ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The sensitivity of fruit fungal pathogens to natamycin has previously been shown in recent years. For instance, a concentration of 20 mg L −1 natamycin could inhibit mycelial growth of A. alternata and Fusarium semitectum (Cong et al, 2007); 2.5 mg L −1 natamycin completely inhibited mycelial growth and sclerogenesis of S. sclerotiorum (Ojaghian et al, 2020); and the minimum inhibitory concentrations of natamycin were 5.0 to 10.0 mg L −1 for mycelial growth and 0.7 to 1.0 mg L −1 for spore germination of Botrytis cinerea (Saito et al, 2020). The above results implicated that natamycin has strong antifungal action in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of fruit fungal pathogens to natamycin has previously been shown in recent years. For instance, a concentration of 20 mg L −1 natamycin could inhibit mycelial growth of A. alternata and Fusarium semitectum (Cong et al, 2007); 2.5 mg L −1 natamycin completely inhibited mycelial growth and sclerogenesis of S. sclerotiorum (Ojaghian et al, 2020); and the minimum inhibitory concentrations of natamycin were 5.0 to 10.0 mg L −1 for mycelial growth and 0.7 to 1.0 mg L −1 for spore germination of Botrytis cinerea (Saito et al, 2020). The above results implicated that natamycin has strong antifungal action in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, natamycin‐resistant filamentous fungi have not been found yet, and fungi of resistance to other fungicides could still be restrained by natamycin (Saito et al, 2020). Previous studies revealed that natamycin displayed an inhibitory effect against Alternaria alternata , Colletotrichum acutatum and Sclerotinia sclerotiorum (Haack et al, 2018; Ojaghian et al, 2020; Wang et al, 2021). And natamycin also showed a suppression effect towards several citrus pathogens (Chen et al, 2021; Saito et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to longterm extensive application of chemical fungicides, pathogens have gradually evolved resistance, and pesticide residues can have negative impacts on human health and the environment (Huzar-Novakowiski et al, 2017). Therefore, biocontrol is an alternative to chemical control strategies, including the use of antagonistic bacteria, fungi, actinomycetes and virions, as well as their secondary metabolites and volatile organic compounds (Chacon-Orozco et al, 2020;Ojaghian et al, 2020b). Biological control agents (BCAs) are considered promising alternative management approaches that can address fungicide resistance while minimizing environmental pollution (Abdullah et al, 2008).…”
Section: Introductionmentioning
confidence: 99%